Identification of soil and biological factors in crop rotation systems with significance to wheat crop performance in the Overberg production area of South Africa - Human, Hans Jurie (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScAgric (Agronomy)--University of Stellenbosch, 2008.